2020
DOI: 10.1590/1981-6723.08919
|View full text |Cite
|
Sign up to set email alerts
|

Accountability in agricultural governance and food security in Nigeria

Abstract: This study explores the relationship between agricultural governance and food security in Nigeria and employs two main approaches: descriptive and econometric. The econometric approach engages Autoregressive Distribution Lag (ARDL) in examining the long-run relationship between the indicators of food security and agricultural governance for the period 1985 to 2016. The results show that in the long-run, agricultural performance contribute to food security in Nigeria. The findings from the descriptive analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Accountability in agricultural governance has also be identified in addition to increased funding as vehicle for the attainment of food security. This was the view of [19]. Using descriptive and econometric tools, they found that improved agricultural production will in the long run positively aid achievement of food security in Nigeria, But that in the short run, there is a significant increase in the number of undernourished people as well as overall increase in the population of the country.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Accountability in agricultural governance has also be identified in addition to increased funding as vehicle for the attainment of food security. This was the view of [19]. Using descriptive and econometric tools, they found that improved agricultural production will in the long run positively aid achievement of food security in Nigeria, But that in the short run, there is a significant increase in the number of undernourished people as well as overall increase in the population of the country.…”
Section: Empirical Literaturementioning
confidence: 99%
“…This shares similarity with ( Anderson and Sun, 2017 ; Bowers et al., 2017 ), who emphasise reviewing existing leadership styles to acknowledge their overlaps and the creation of a new theory. Such leadership approach results to connected thinking and actions that strive to satisfy the interest of all stakeholders who are affected by leadership decisions (see, Midgley, 2000 ; Midgley and Ochoa-Arias, 2012 ; Ufua et al., 2018 ; Osabohien et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to risks, shocks and low welfare incentives are the main problems faced by agricultural households in Africa (Osabohien et al, 2020a(Osabohien et al, , 2020b(Osabohien et al, , 2020cMatthew et al, 2019aMatthew et al, , 2019bOsabohien et al, 2019aOsabohien et al, , 2019bOmiti & Nyanamba, 2007). This is as a result of the fact that in Africa various policy and institutional reforms have been less than satisfactory in their outcomes (Beecroft et al, 2020;Igharo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…African countries have in the past neglected the rural and agricultural sectors while giving priority to the industrial and urban sectors. The contribution of agriculture to economic growth through the production of food, supply of raw materials to industries, employment generation, provision of market for goods and service sector amongst others cannot be adequately captured without emphasis to the rural sector (Matthew et al, 2018;Osabohien et al, 2020aOsabohien et al, , 2020bOsabohien et al, , 2020c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation